Undergraduate PAASCU re-accreditation - De La Salle University, Manila (Animo Repository, 2018)
The Undergraduate Programs of the College of Liberal Arts (CLA), School of Economics (SOE), Br. Andrew Gonzalez FSC College of Education (BAGCED), Ramon V. del Rosario College of Business (RVRCOB), College of Computer Studies (CCS), and the College of Science (COS), underwent its PAASCU re-accreditation on November 28-29, 2018. The Chancellor requested the academic community for the support and cooperation.